Optimization of Aquaponic System for Sustainable Food Production on Limited Land in Pesanggrahan Village, Kesugihan District, Cilacap Regency - Syifa, Zahra Nur Asy; Aulia, Revalina Putri; Saputro, Fani Nur Dwi; Listyawati, Indriyani Eka; Akmaludin, Muammara; Putri, Najwa Salsabila; Nabila, Chella Putri; Khairunnisa, Andina; Kusumaningtyas, Denisa Ridha; Wiguna, Tangguh Akhmal; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Aquaponics is the integration of aquaculture and hydroponics systems that can be a solution to overcome land and water limitations and improve food security. The principle of aquaponics utilizes a recirculation system, where water from the fish tank is recirculated back into the tank through a filtration process. This study aims to optimize the aquaponics system to enhance sustainable food production on limited land. The method combines tilapia fish farming with hydroponic cultivation of water spinach. Catfish waste water is channeled to hydroponic spinach and bok choy plants through a biofilter that breaks down waste into nitrates and nitrites as plant nutrients. After filtration and achieving high dissolved oxygen levels, the water is recirculated back to the catfish pond. The research results show that the aquaponics system can save up to 90% water compared to conventional methods, supports optimal plant growth, and utilizes fish waste as natural fertilizer. In addition to providing ecological benefits, this system also has the potential to increase income through dual harvests of fish and vegetables. Thus, aquaponics is one of the innovative and sustainable solutions to support food security, especially in areas with limited land.